The impact of ICT and FDI as drivers to economic growth in asean-8 countries: a panel regression analysis - Noraina Mazuin, Sapuan; Mohammad Rahmdzey, Roly (Penerbit Universiti Malaysia Pahang, 2021)
Over the last few years, information and communication technology (ICT) has become a key catalyst for economic growth. The durability of this technology is demonstrated by the rapid proliferation of the Internet, mobile phones and cellular networks across the globe. However, among economic scholars, the question of exactly how the spread of ICT affects economic development and FDI, especially in ASEAN countries with differences in levels of income, remains unanswered. The aim of this study was essentially to explore the relationship between ICT dissemination, FDI and economic growth in ASEAN-8 countries. By using data from 2003 to 2017, the panel regression analysis was used to evaluate these relationships. The results showed that the dissemination of ICT and FDI are important and they have a positive effect on the ASEAN-8 countries’ economic development.